Ragam Perspektif Profesi Guru - Misnatun Misnatun (Tafhim Al-'Ilmi, 2019)
The meaning of teachers is related for the life philosophy of a community. Which generally secular western society tends to regard the teacher as an sich companion for students, their interests are not more than just the transfer of knowledge. Even in a more extreme level, religious symbols strictly prohibited into the classrooms. The fact is truly turned to the experience and teachings of Islam. In Islam teachers are not only seen as a 'bank' whose job is only saving and transfer of knowledge, but more that, the teacher is the one who has the moral responsibility, spiritual, and intellectual integrally. Abstrak Makna guru berhubungan erat dengan falsafah hidup suatu masyarakat. Masyarakat barat yang umumnya sekuler cenderung memandang guru sebagai teman bagi peserta didik, kepentingannya tidak lebih dari sekedar transfer pengetahuan. Bahkan dalam tataran yang lebih ekstrim, simbol-simbol keagamaan dilarang ketat masuk ke dalam ruang-ruang kelas. Kenyataan tersebut sungguh berbalik dengan pengalaman dan ajaran Islam. Dalam Islam guru tidak hanya dipandang sebagai ‘bank’ pengetahuan yang tugasnya hanya menyimpan dan mentrasfer pengetahuan, tetapi lebih dari itu, guru adalahorang yang memiliki tanggungjawab moral, spiritual, dan intelektual secara integral.